UNLOCKING CAREER POTENTIAL: THE MEDIATING ADVERSITY QUOTIENT IN PARENTAL SUPPORT TO CAREER ADAPTABILITY AMONG DUAL CAREER GIG ECONOMY STUDENTS - Heryanda, Komang Krisna; Mayasari, Ni Made Dwi Ariani; Telagawathi, Ni Luh Wayan Sayang (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study examines the effect of parental support on adversity quotient and career adaptability in dual career students who work in the gig economy sector. The main focus in this research is how parental support​ can strengthen the adversity quotient and career adaptability of students in facing academic challenge and uncertainty​ in the world of gig economy work. This research makes a new contribution by showing that parental support plays an important role in increasing the adversity quotient and career adaptability, which is still not widely explored​ in literature of dual career student in the gig economy. The results of research from a sample of 196 students who were processed quantitatively through SEM-PLS analysis showed that students who get parental support​ will have a higher adversity quotient and more easily adapt to changes that occur in the world of work gig economy. This study conclude that parental support help student reduce stress, increase self-confidence, and facilitate better career decision-making. The implications of this study are relevant to the majority of 21-23 years old, where students in phase are forming a career identity and often face uncertainty their career direction. Parental support provides support that strengthens curiosity and concern in students' career adaptability. Therefore, the research underlines the importance of parental support reinforced by university counselling guidance in providing in-depth and holistic academic and career self-development programs, especially for dual career students involved in the gig economy.